Diseño de un sistema de monitoreo de vibraciones online para la detección y el diagnóstico de fallas de un motor trifásico de inducción - Corcuera Cisneros, Lucio Pedro (2019)
Currently there is a great need to monitor the condition of the industry's threephase induction critical engines. However, the problems of inaccessibility for monitoring, as well as the impossibility of counting, 100% of the time with an inspector and predictive analyst, have required the search of automated systems that facilitate the task. In this research work a solution has been developed for this problem, which is the design of an online vibration monitoring system, which allows the necessary information for the detection of premature failures, the need to have a predictive inspector, and with less work time for the predictive analyst. First a study of the machine, a monitor and a failure mode was carried out. Subsequently, the technique of vibrational analysis applied to monitor the condition of the induction motor was investigated, as well as the necessary instrumentation for an automated system. At the base of the same the monitoring system was designed, as well as the subject of the ISO 10816 standard. Finally, a field test was carried out with the design results, the vibration monitoring was carried out outside the line in an induction motor, checking the efficiency of the system, as well as the vibration analysis potential for the operation of the condition of the induction motors.